WOME: Theory-Based Working Memory Training — A Placebo-Controlled, Double-Blind Evaluation in Older Adults - Weicker, Juliane; Hudl, Nicole; Frisch, Stefan; Lepsien, Jöran; Mueller, Karsten; Villringer, Arno; Thöne-Otto, Angelika (Frontiers in Aging Neuroscience, 2018)
Background: Scientifically evaluated cognitive intervention programs are essential to meet the demands of our increasingly aging society. Currently, one of the “hottest” topics in the field is the improvement of working memory function and its potential impact on overall cognition. The present study evaluated the efficacy of WOME, a theory-based WOrking MEmory training program, in a double-blind, placebo-controlled, and randomized controlled trial (www.drks.de, DRKS00013162). Methods: N = 60 healthy older adults were allocated to 1) the WOME intervention, 2) an active low-level intervention, or 3) a passive control group. Overall, the intervention groups practiced twelve sessions of 45 min within four weeks of their respective training. Transfer effects were measured via an extensive battery of neuropsychological tests and questionnaires both pre-/post-training and at a three-month follow-up. Results: WOME led to a significant improvement in working memory function, demonstrated on a non-trained near transfer task and on two different composite scores with moderate to large effect sizes. In addition, we found some indication of relevant impact on everyday life. The effects were short-term rather than stable, being substantially diminished at follow-up with only little evidence suggesting long-term maintenance. No transfer effects on other cognitive functions were observed. Conclusions: WOME is an appropriate and efficient intervention specifically targeting the working memory system in healthy older adults.